Methylnaltrexone for the management of unwanted peripheral opioid effects. Issue 4 (July 2008) - Holzer, Peter
For many a patient suffering from moderate to severe pain, opioid analgesics offer the anxiously sought-after relief, but at a high price. While the pain is wearing off, distressful constipation, abdominal discomfort, nausea and urinary retention ensue. These unwanted effects have been difficult to deal with, and the laxatives that are usually prescribed ameliorate constipation in no more than 50% of the patients receiving opiates. A new treatment concept emerged from the development of opioid receptor antagonists with a peripherally restricted site of action. One of these treatments is methylnaltrexone, which clinical trials have shown to be of benefit in opioid-induced constipation, postoperative ileus and urinary retention, while analgesia remains unabated. The drug is well tolerated and holds great promise in freeing opioid therapy of some of its most-feared adverse aspects. In 2008, methylnaltrexone (Relistor™™) was approved in the USA, Canada and Europe for the treatment of opioid-induced constipation in patients with advanced illness.